2009
DOI: 10.1002/ajmg.b.31046
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms correlate with reduced hippocampal volume in fragile X premutation carriers

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder occurring in male and occasional female carriers of a premutation expansion (55–200 CGG repeats) of the fragile X mental retardation 1 gene (FMR1). This study assessed the relationship between hippocampal volume and psychological symptoms in carriers, both with and without FXTAS, and controls. Volumetric MRI measures, clinical staging, cognitive testing, molecular analysis, and measures of psychological symptoms were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 68 publications
4
63
2
Order By: Relevance
“…Notable amygdala abnormalities in male carriers include an impaired response to fearful faces, a significant negative correlation of amygdala volume with CGG size for the 55-85 repeat range, and grey matter volume loss in men with FXTAS [53][54][55]. Additionally, female carriers displayed a significant negative correlation between the hippocampal volume and severity of anxiety symptoms [56]. Table 1 presents a comparison of FXTAS dementia with other dementias: AD, dementia with Lewy bodies (DLB), behavioral variant of frontotemporal dementia (bv-FTD), Huntington's disease, and Parkinson's disease dementia (PDD) [57][58][59].…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 96%
“…Notable amygdala abnormalities in male carriers include an impaired response to fearful faces, a significant negative correlation of amygdala volume with CGG size for the 55-85 repeat range, and grey matter volume loss in men with FXTAS [53][54][55]. Additionally, female carriers displayed a significant negative correlation between the hippocampal volume and severity of anxiety symptoms [56]. Table 1 presents a comparison of FXTAS dementia with other dementias: AD, dementia with Lewy bodies (DLB), behavioral variant of frontotemporal dementia (bv-FTD), Huntington's disease, and Parkinson's disease dementia (PDD) [57][58][59].…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 96%
“…These regions have been implicated in motor and cognitive functions including coordination and attention [78], frequent difficulties in individuals with FXTAS. In premutation carriers of FraX without FXTAS, reduced volume in a number of regions including the amygdala-hippocampal complex bilaterally [62], the left hippocampus [156] and the left thalamus has been documented [62,157], with a negative correlation between total hippocampal volume and anxiety in female carriers also reported [158,159]. No difference in hippocampal or amygdala volumes between premutation carriers and normal controls has however also been observed [157,158].…”
Section: Premutations Carriers Of Fraxmentioning
confidence: 99%
“…Apart from the abnormal phenotypes associated with the premutation condition, recent studies have focused on the asymptomatic state of FXP carriers and their potentially relevant preclinical features such as brain structural correlates or neuropsychological and behavioral abnormalities (Adams et al 2010;Berry-Kravis et al 2007; Goodrich- Hunsaker et al 2011a,b;Hashimoto et al 2011a,b;Hessl et al 2005;Hunter et al 2008aHunter et al ,b, 2009Johnston et al 2001;Roberts et al 2009;Rodriguez-Revenga et al 2008). In a recent study by Hashimoto et al (2011b), the authors found a significant grey matter reduction in the cerebellum of asymptomatic male FXP carriers compared with healthy controls without the premutation.…”
mentioning
confidence: 99%
“…In a recent study by Hashimoto et al (2011b), the authors found a significant grey matter reduction in the cerebellum of asymptomatic male FXP carriers compared with healthy controls without the premutation. Some recent studies have tried to find brain structural correlates of proposed neuropsychological FXP phenotypes in carriers with and without FXTAS (Adams et al 2010;Hashimoto et al 2011a). However, the underlying brain function of asymptomatic FXP carriers in a preclinical state is still poorly understood.…”
mentioning
confidence: 99%